Comparative transcriptome analysis of isonuclear-alloplasmic lines unmask key transcription factor genes and metabolic pathways involved in sterility of maize CMS-C - Chuan Li; Zhuofan Zhao; Yongming Liu; Bing Liang; Shuxian Guan; Hai Lan; Jing Wang; Yanli Lu; Moju Cao (PeerJ, 2017)
Although C-type cytoplasmic male sterility (CMS-C) is one of the most attractive tools for maize hybrid seed production, the detailed regulation network of the male sterility remains unclear. In order to identify the CMS-C sterility associated genes and/or pathways, the comparison of the transcriptomes between the CMS-C line C48-2 and its isonuclear-alloplasmic maintainer line N48-2 at pollen mother cell stage (PS), an early development stage of microspore, and mononuclear stage (MS), an abortive stage of microspore, were analyzed. 2,069 differentially expressed genes (DEGs) between the two stages were detected and thought to be essential for the spikelet development of N48-2. 453 of the 2,069 DEGs were differentially expressed at MS stage between the two lines and thought to be participated in the process or the causes of microspore abortion. Among the 453 DEGs, 385 (84.99%) genes were down-regulated and only 68 (15.01%) genes were up-regulated in C48-2 at MS stage. The dramatic decreased expression of the four DEGs encoding MYB transcription factors and the DEGs involved in “polyamine metabolic process”, “Cutin, suberine and wax biosynthesis”, “Fatty acid elongation”, “Biosynthesis of unsaturated fatty acids” and “Proline metabolism” might play an important role in the sterility of C48-2. This study will point out some directions for detailed molecular analysis and better understanding of sterility of CMS-C in maize.